ASSOCIATION BETWEEN CHEMOTACTIC CYTOKINE RECEPTOR 5 (CCR5) GENE PROMOTER (59029 G/A) POLYMORPHISM AND DIABETIC NEPHROPATHY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Tun, Sai Thiha; Kyaw, Theingi; Htut, Zaw Min; Htun, Nyan Sint; Naing, Thet (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Diabetic nephropathy is the leading cause of end-stage renal disease. Despite optimal glucose and blood pressure control, many patients still develop diabetic nephropathy. These patients might have some genetic risk factors associated with diabetic nephropathy. METHODOLOGY Ninety-eight patients with type 2 diabetes mellitus were included in this cross-sectional case-control study, which was conducted at No. (2) Military Hospital (500-bedded), Yangon. The study aimed to investigate the association between chemotactic cytokine receptor 5 (CCR5) gene promoter 59029 G/A polymorphism and diabetic nephropathy in patients with type 2 diabetes mellitus. Genotype frequencies (GG, GA, AA) were determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Serum creatinine was measured to calculate the estimated glomerular filtration rate (eGFR); urine creatinine and urine albumin were measured to calculate urine albumin to creatinine ratio (ACR). RESULTS CCR5 59029 G/A genotype frequencies, namely, GG, GA and AA were found in 28.6%, 49.0% and 22.4%, respectively, in patients with diabetic nephropathy, and 30.6%, 44.9% and 24.5%, respectively in those without diabetic nephropathy. G allele frequency was 53.1%, and A allele frequency was 46.9% respectively, in both groups. Genotype frequencies did not deviate from Hardy-Weinberg equilibrium (HWE: χ2 = 0.326, p = 0.567). The odds ratio (OR) and 95% confidence interval (95% CI) were used to analyze the association of genotypes and alleles with diabetic nephropathy. The clinical characteristics were not significantly different between both groups (p >0.05), apart from HbA1c and renal profile. The statistically significant association between the CCR5 59029 G/A genotypes and diabetic nephropathy was not found in different genetic models (co-dominant, dominant, recessive and allelic models) (p >0.05). CONCLUSION The association between CCR5 gene promoter 59029 G/A polymorphism and diabetic nephropathy in patients with type 2 diabetes mellitus was not found in this study population.